The seed industry in Pakistan: Regulations, politics and entrepreneurship - Rana, Muhammad Ahsan (International Food Policy Research Institute, 2014)
This paper critically examines the legislative and institutional framework that governs seed provision in Pakistan, underscoring the need for policy reform in key areas of variety release procedures, intellectual property rights and quality control. The paper also systematically documents the current state of seed provision for various major and minor crops. It provides up-to-date data-insofar as these are available in the public domain-on variety development, seed requirement, production, and sale for various crops; identifies various actors in the public and private sectors; and examines their political and economic interests in continuing or changing the existing system.